A inova????o como instrumento de suporte ?? ecoefici??ncia em eventos: uma vis??o al??m do espet??culo - Guimar??es, Paulo Ferreira (2017)
This research, through a case study carried out in a company providing services in the audiovisual area, sought, through the application of sustainable project management, to analyze the influence of innovations on ecoefficiency in events, especially corporate events. The event sector begins to move towards sustainable events, in which the use of recycling techniques, selective collection of waste, conscious use of water, even more with the current water crisis, become increasingly common practices and that corroborate to satisfy the concept of the Triple Bottom Line (TBL). In order to anticipate and mitigate to the maximum the problems that negatively affect and influence the TBL, this study proposed a prior analysis of what is possible to mitigate during the execution of the event and not only treat the post-event, that is. After the generation of waste. One of the ways to achieve this goal is through innovations, which are presented in a dynamic way and promote a constant evolution, whether in equipment or processes. The application of these innovations was the object of study in this work, with the intention of showing how they can be applied to help in the ecoefficiency of the events. With a comparative approach between solutions and equipment that do not use innovations aligned with sustainable demands and others that have such requirements, we sought to analyze how innovations can collaborate with events to become more assertive about what we all seek, not Only in events, but for our planet, which is to use resources in a rational way, so that it does not compromise the needs of future generations. The case study developed through a qualitative and exploratory research sought to find correlations between the innovations and their potential to add value, both to clients contracting the events and to the participants of the same, either through the return on the investment made or through the perception of value observed by the participating public. As a basis for this study framework, several measurements were carried out and analyzed, comparing the proposed solutions, analyzing their collaborative potential for ecoefficiency in events. The main result was a total collaboration of the eco-efficient innovations proposed for sustainability in events. The analyzes showed that all the innovations proposed were totally satisfactory in the two dimensions that cover eco-efficiency, that is, the environmental and the economic.